Dating brittle tectonic movements with cleft monazite: Fluid‐rock interaction and formation of REE minerals. Issue 5 (1st October 2013) - Berger, A.; Gnos, E.; Janots, E.; Whitehouse, M.; Soom, M.; Frei, R.; Waight, T. E.
Abstract [1] Two millimeter‐sized hydrothermal monazites from an open fissure (cleft) that developed late during a dextral transpressional deformation event in the Aar Massif, Switzerland, have been investigated using electron microprobe and ion probe. The monazites are characterized by high Th/U ratios typical of other hydrothermal monazites. Deformation events in the area have been subdivided into three phases: (D1) main thrusting including formation of a new schistosity, (D2) dextral transpression, and (D3) local crenulation including development of a new schistosity. The two younger deformational structures are related to a subvertically oriented intermediate stress axis, which is characteristic for strike slip deformation. The inferred stress environment is consistent with observed kinematics and the opening of such clefts. Therefore, the investigated monazite‐bearing cleft formed at the end of D2 and/or D3, and during dextral movements along NNW dipping planes. Interaction of cleft‐filling hydrothermal fluid with wall rock results in rare earth element (REE) mineral formation and alteration of the wall rock. The main newly formed REE minerals are Y‐Si, Y‐Nb‐Ti minerals, and monazite. Despite these mineralogical changes, the bulk chemistry of the system remains constant and thus these mineralogical changes require redistribution of elements via a fluid over short distances (centimeter). Low‐grade alteration enables local redistribution of REE, related to the stability of the accessory phases. This allows high precision isotope dating of cleft monazite. 232Th/208Pb ages are not affected by excess Pb and yield growth domain ages between 8.03 ± 0.22 and 6.25 ± 0.60 Ma. Monazite crystallization in brittle structures is coeval or younger than 8 Ma zircon fission track data and hence occurred below 280°C.